The differences in motoric basic and situational motoric tests to young basketball players - Hazir Salihu; Florian Miftari (Kazimierz Wielki University, 2018)
In this study-experiment are treated 14-15 years old young basketball players includes 66 entities of males (33 are active while 33 are not active), who are subjected to certain tests from the trainer, who besides learning process exercise basketball in different basketball schools in the city of Prishtina. The experiment includes 10 variables, 5 from those variables are from the basic motor performance and 5 other variables are from situational skills. The data was analyzed by mathematical statistical package, SPPS program, version 23.0 for windows. Scientific research is done in the composition of the motoric basic and motoric situational tests. The processing of results is done by T-test for independent entities. First purpose of this study- experimentation, is to conclude the presentation of changes in some features and basic and situational motor skills at basketball players aged 14-15 years. The second purpose of this study will be defined, certification of variables on some basic and situational motor skills at young basketball players. Through this experiment are observed changes in motor space, movements in situational tests which are in favor of the group with active basketball players.